PARENTAL PERCEPTIONS OF EMPATHY AMONG TYPICALLY DEVELOPING CHILDREN IN A FULLY INCLUSIVE SCHOOL: A PHENOMENOLOGICAL - Nur Azizah; Tsara Afra Inna Devi; Euis Nurhidayati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
Inclusive education plays a strategic role in fostering social empathy among children, particularly non-special needs children who interact with peers with special needs. This study explores parents' perceptions of social empathy development in non-special needs children at Aluna Montessori Kindergarten Jakarta, which implements a full inclusion model. Employing a descriptive phenomenological approach, five parents were selected through purposive sampling as participants. Data collection was conducted through semi-structured interviews and analyzed using Colaizzi's phenomenological procedure. Data validity was maintained through source triangulation and member checking with participants. Research findings indicate that daily interaction experiences within a fully inclusive environment facilitate the development of affective empathy, cognitive empathy, and prosocial behavior in non-special needs children. Children demonstrate spontaneous emotional responses, understanding of peers' varying needs, and attitudes of tolerance and acceptance toward diversity that become internalized both within school contexts and broader social settings. Findings underscore the significance of inclusive social experiences from early childhood periods in supporting authentic and sustainable social empathy formation in children.